Transcriptional Changes in Pulmonary Phagocyte Subsets Dictate the Outcome Following Interaction With The Fungal Pathogen Cryptococcus neoformans - Hawkins, Ashlee N.; Determann, Brenden F.; Nelson, Benjamin N.; Wozniak, Karen L. (Frontiers in Immunology, 2021)
With over 220,000 cases and 180,000 deaths annually, Cryptococcus neoformans is the most common cause of fungal meningitis and a leading cause of death in HIV/AIDS patients in Sub-Saharan Africa. Either C. neoformans can be killed by innate airway phagocytes, or it can survive intracellularly. Pulmonary murine macrophage and dendritic cell (DC) subsets have been identified in the naïve lung, and we hypothesize that each subset has different interactions with C. neoformans. For these studies, we purified murine pulmonary macrophage and DC subsets from naïve mice – alveolar macrophages, Ly6c- and Ly6c+ monocyte-like macrophages, interstitial macrophages, CD11b+ and CD103+ DCs. With each subset, we examined cryptococcal association, fungicidal activity, intracellular fungal morphology, cytokine secretion and transcriptional profiling. Results showed that all subsets associate with C. neoformans, but only female Ly6c- monocyte-like macrophages significantly inhibited growth, while male CD11b+ DCs significantly enhanced fungal growth. In addition, cytokine analysis revealed that phagocyte polarization is not responsible for the differences in fungicidal activity observed. Imaging flow cytometry showed differing ratios of cryptococcal morphologies, c-shaped or budding, depending on phagocyte subset. RNA sequencing analysis revealed the up regulation and downregulation of many genes, including immunological pathways and pathways relating to relating to metabolic activity. Future studies gaining a more in-depth understanding on the functionality of individual genes and pathways specific to permissive and non-permissive pulmonary phagocytes will allow identification of key targets when developing therapeutic strategies to prevent cryptococcal meningitis.